Role of computed tomography in the evaluation of schwannoma in the posterior cranial fossa (Bangladesh Medical Journal, 2014)
Schwannoma is one of the most common posterior cranial fossa tumours. Normal skull radiograph may not give any clue to diagnosis and further investigation with computed tomography or magnetic resonance imaging is necessary. This cross sectional study was carried out in the department of neurosurgery and the department of radiology and Imaging, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh during the period from July 2009 to June 2011 to evaluate the role of computed tomography in the diagnosis of schwannoma in the posterior cranial fossa. Total eighty nine patients with clinical features of posterior cranial fossa tumour were enrolled in this study. Mean age of the patients was 29.15±19.64 years. Computed tomography scan revealed that 38.2% had schwannoma, 24.7% had meningioma, 21.3% had astrocytoma, 15.7% medulloblastoma, 10.1% had brain stem glioma, 5.6% had ependymoma and for the rest 4.4%, 1.1% of each had epidermoid, metastatic, hemangioblastoma and others. After histopathological diagnosis 36.0% patients had schwannoma, 19.1% had astrocytoma, 15.7% had medulloblastoma, 11.2% had meningioma, 7.9% had brain stem glioma, 5.6% had ependymoma and rest 4.4% had epidermoid, metastatic, hemangioblastoma and others. Sensitivity of computed tomography to diagnose schwannoma was 100.0%, specificity 96.5%, positive predictive value 94.1%, negative predictive value 100.0% and accuracy 97.8%. It can therefore be concluded that computed tomography is a useful modality in the evaluation of schwannoma in the posterior cranial fossa. DOI: http://dx.doi.org/10.3329/bmj.v42i3.19002 Bangladesh Med J. 2013 Sept; 42 (3): 85-88